Exploring mechanisms of increased cardiovascular disease risk with antipsychotic medications: Risperidone alters the cardiac proteomic signature in mice. (February 2020) - Beauchemin, Megan; Geguchadze, Ramaz; Guntur, Anyonya R.; Nevola, Kathleen; Le, Phuong T.; Barlow, Deborah; Rue, Megan; Vary, Calvin P.H.; Lary, Christine W.; Motyl, Katherine J.; Houseknecht, Karen L.
Graphical abstract: Abstract: Atypical antipsychotic (AA) medications including risperidone (RIS) and olanzapine (OLAN) are FDA approved for the treatment of psychiatric disorders including schizophrenia, bipolar disorder and depression. Clinical side effects of AA medications include obesity, insulin resistance, dyslipidemia, hypertension and increased cardiovascular disease risk. Despite the known pharmacology of these AA medications, the mechanisms contributing to adverse metabolic side-effects are not well understood. To evaluate drug-associated effects on the heart, we assessed changes in the cardiac proteomic signature in mice administered for 4 weeks with clinically relevant exposure of RIS or OLAN. Using proteomic and gene enrichment analysis, we identified differentially expressed (DE) proteins in both RIS- and OLAN-treated mouse hearts (p < 0.05), including proteins comprising mitochondrial respiratory complex I and pathways involved in mitochondrial function and oxidative phosphorylation. A subset of DE proteins identified were further validated by both western blotting and quantitative real-time PCR. Histological evaluation of hearts indicated that AA-associated aberrant cardiac gene expression occurs prior to the onset of gross pathomorphological changes. Additionally, RIS treatment altered cardiac mitochondrial oxygen consumption and whole body energy expenditure. Our study provides insight into the mechanisms underlying increased patient risk for adverse cardiac outcomes with chronic treatment of AA medications.